2021
DOI: 10.14202/vetworld.2021.446-451
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and distribution of soil-transmitted helminth infection in free-roaming dogs in Bali Province, Indonesia

Abstract: Background and Aim: Several free-roaming dogs can be easily found in the public areas of Bali. They go out in search of foods and friends and defecate everywhere. In general, these groups of dogs do not receive good healthcare from their owners and are generally threatened by some disease-causing organisms, especially helminths. This study was conducted to identify and measure the prevalence of soil-transmitted helminths (STHs) that cause infection in free-roaming dogs in Bali Province, Indonesia. Materials a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
1
3
0
1
Order By: Relevance
“…were found to infect dogs more in Gunung Kidul Regency. The same thing was found in several previous studies that Ancylostoma spp and Toxocara canis infections were more commonly found in dogs that were released free or not in cages (18,20,22).…”
Section: Questionnaire and Data Analysissupporting
confidence: 87%
“…were found to infect dogs more in Gunung Kidul Regency. The same thing was found in several previous studies that Ancylostoma spp and Toxocara canis infections were more commonly found in dogs that were released free or not in cages (18,20,22).…”
Section: Questionnaire and Data Analysissupporting
confidence: 87%
“…The overall prevalence of helminthic infections in dogs and cats was 61.11% and 53.80%, respectively. The prevalence was high compared to other parts of Indonesia (15.09%-57.14%) [48][49][50] or other Available at www.veterinaryworld.org/Vol.16/May-2023/17.pdf countries, such as Ghana (52.6%) [51] and Thailand (40.1%) [52]. Lower prevalence levels have also been reported in cats in other studies from Indonesia (1.7%-37.8%) [53][54][55] and Thailand (33.9%) [52].…”
Section: Discussionmentioning
confidence: 85%
“…The prepared tubes were allowed to stand for 2-3 min so that the worm eggs would float to the surface. Samples were transferred to glass slides, cover glass was placed over the surface of the liquid, and they were observed with a microscope (Olympus CX21, Japan) under 100× magnification [ 47 , 48 ].…”
Section: Methodsmentioning
confidence: 99%